Multisystem Inflammatory Syndrome in Children in a 15-Year-Old Male with a Retropharyngeal Phlegmon. (19th November 2020) - Han, Paul; Douillard, Jelena; Cheng, Jerry; Ramanathan, Anusha; Tieu, David; Degner, Timothy
Abstract : This is a case of a 15-year-old male with an initial diagnosis of a retropharyngeal phlegmon who ultimately developed new symptoms and laboratory findings consistent with MIS-C. This case report demonstrates an atypical initial presentation for MIS-C that has not been reported in the literature.